Recovery and balance of field-applied labelled fertilizer nitrogen by maize and barley on sandy soil - Yusop, Mohd Khanif; Cleemput, O. Van; Baert, L. (1982)
In a field experiment, under standard management practices, the uptake and balance of labelled N03-N fertilizer was studied. On a 4 x 4 m₂ plot, N-15 labelled KN03 was applied at a rate of 83 kg/Ha and 48 kg/Ha to maize and barley respectively. At harvesting time, the treated plots were subdivided into 6 subplots for maize and 9 subplots for barley, providing data on micro-variability of the treated plots. It was found that 18.8 % of the N in the maize plants was derived from the fertilizer while it was 25.4 % in the barley plants. The percentage of the applied nitrogen fertilizer recovered by the plants was 46.6 % and 37.7 % in maize and barley respectively. The coefficient of variation for the plant recovery results was 21 % for the maize experiment and 26 % for the barley experiment. The amount of fertilizer nitrogen remaining in the soil after harvest was 21.1 % for the maize plot and 39.8 % for the barley plot. This nitrogen was mostly found in the top 50 em of the profile for the barley plot; while for the maize plot, it was almost equally distributed throughout the profile up to a depth of 1 m. This also means that the amount of fertilizer nitrogen unaccounted for was 31.4 % for maize and 22.3 % for barley. 8y t-test and by F-test it was found that the data of the two experimental fields did not differ significantly from data collected at random outside the experimental plot. So, extrapolation of the results to the whole field is justified.